ANALISIS KEMANFAATAAN ALAT PEMBERSIH ASAP ROKOK MENGGUNAKAN ARDUINO NANO DAN SENSOR MQ2 - Riana Safitri; Imas Fitria Kusuma (Jurnal Teknologi Informasi, Ilmu Komputer dan Manajemen, 2022)
Abstract- Air pollution due to cigarette smoke is very dangerous for human health. In addition to damaging yourself, cigarette smoke can also harm other people who breathe in the smoke. Some customers at Jolie's salon are active smokers. Even though cigarette smoke is one of the reasons why customers are uncomfortable with the presence of cigarette smoke, Jolie's salon policy creates research that can understand each customer to keep each other comfortable, this tool is designed to use the mq2 sensor and Arduino nano as the main controller resulting from the relay work process. and the mq2 sensor and fan as an air purifier. Arduino nano conditions the mq2 sensor as input and relay as output. The product is tested using a Dimension Of Quality For Good tester which is declared successful because the Benefit test value is reliable with a value above 75, which is 78.88 which means it is acceptable and beneficial for the community, from the recapitulation of the test value. The product is obtained from the percentage with the highest value of 83.3%, then the product is declared valid.